The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jace.18773
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and phase transition of uranium‐doped LaxGd2−xZr2O7 transparent ceramics: A prospective neutron detection material

Abstract: Via vacuum sintering, 2 mol% uranium‐doped LaxGd2−xZr2O7 (x = 2, 1.6, 1, and 0.4) transparent ceramics with Ca2+ as charge compensator was first fabricated by solid‐state reaction. X‐ray diffraction results of as‐prepared powders and ceramic samples demonstrate that the phase transition from defective fluorite to pyrochlore occurs with the increase of x. Optical in‐line transmittance spectrum shows that four ceramic samples have good in‐line transmittance (nearly 80% from 700 to 2200 nm), especially the U:La1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…[41][42][43][44][45][46] Though a number of reports regarding substitution of radionuclides at the A site of the pyrochlore prevail, very insignificant work has been reported with respect to substitution at the B site. 42,47,48 In our recent report we utilized Y 2 Ti 2 O 7 as the base matrix and doped U and Ce at the Y site. 49 We observed that under reducing conditions we could incorporate 10 mol% of U.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45][46] Though a number of reports regarding substitution of radionuclides at the A site of the pyrochlore prevail, very insignificant work has been reported with respect to substitution at the B site. 42,47,48 In our recent report we utilized Y 2 Ti 2 O 7 as the base matrix and doped U and Ce at the Y site. 49 We observed that under reducing conditions we could incorporate 10 mol% of U.…”
Section: Introductionmentioning
confidence: 99%